2015
DOI: 10.1097/mao.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Dysfunctions in Patients With Chronic Subjective Tinnitus

Abstract: Although a higher prevalence of neck dysfunction was found in the CST group, neck dysfunction is often in non-CST patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 18 publications
(20 reference statements)
6
50
0
2
Order By: Relevance
“…This is in accordance with the findings of a recent study [11] that found no differences in CCFT comparing neck related symptoms in CST and non-CST patients. No information is available on differences in CCFT between CST patients and asymptomatic controls, which could be interesting, because in other neck related populations such as cervicogenic headache patients, a significant difference in CCFT could be found between patients and asymptomatic controls [16].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in accordance with the findings of a recent study [11] that found no differences in CCFT comparing neck related symptoms in CST and non-CST patients. No information is available on differences in CCFT between CST patients and asymptomatic controls, which could be interesting, because in other neck related populations such as cervicogenic headache patients, a significant difference in CCFT could be found between patients and asymptomatic controls [16].…”
Section: Discussionsupporting
confidence: 94%
“…These findings might explain the ability of some tinnitus patients to modulate their tinnitus by certain head or neck movements. For example: some patients indicate that their tinnitus worsens when performing a combined cervical spine extension and rotation [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of tinnitus is called somatic tinnitus and has been described in 36–43% of a population with subjective tinnitus (Abel and Levine, 2004; Michiels et al, 2015). A physiological explanation is proposed by several animal studies, which have found connections between the somatosensory system of the cervical spine and temporomandibular area on the one hand and the cochlear nuclei (CN) on the other hand (Pfaller and Arvidsson, 1988; Zhan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%